Insights on Gut and Skin Wound Microbiome in Stranded Indo-Pacific Finless Porpoise (Neophocaena phocaenoides) - Chengzhang Li; Huiying Xie; Yajing Sun; Ying Zeng; Ziyao Tian; Xiaohan Chen; Edmond Sanganyado; Jianqing Lin; Liangliang Yang; Ping Li; Bo Liang; Wenhua Liu (Microorganisms, 2022)
The gut microbiome is a unique marker for cetaceans’ health status, and the microbiome composition of their skin wounds can indicate a potential infection from their habitat. Our study provides the first comparative analysis of the microbial communities from gut regions and skin wounds of an individual Indo-Pacific finless porpoise (Neophocaena phocaenoides). Microbial richness increased from the foregut to the hindgut with variation in the composition of microbes. Fusobacteria (67.51% ± 5.10%), Firmicutes (22.00% ± 2.60%), and Proteobacteria (10.47% ± 5.49%) were the dominant phyla in the gastrointestinal tract, while Proteobacteria (76.11% ± 0.54%), Firmicutes (22.00% ± 2.60%), and Bacteroidetes (10.13% ± 0.49%) were the dominant phyla in the skin wounds. The genera Photobacterium, Actinobacillus, Vibrio, Erysipelothrix, Tenacibaculum, and Psychrobacter, considered potential pathogens for mammals, were identified in the gut and skin wounds of the stranded Indo-Pacific finless porpoise. A comparison of the gut microbiome in the Indo-Pacific finless porpoise and other cetaceans revealed a possible species-specific gut microbiome in the Indo-Pacific finless porpoise. There was a significant difference between the skin wound microbiomes in terrestrial and marine mammals, probably due to habitat-specific differences. Our results show potential species specificity in the microbiome structure and a potential threat posed by environmental pathogens to cetaceans.